2020
DOI: 10.21203/rs.3.rs-48449/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitophagy Promotes Sorafenib Resistance through Hypoxia-Inducible ATAD3A Dependent Axis

Abstract: Background: The identification of novel targets for recovering sorafenib resistance is pivotal for Hepatocellular carcinoma (HCC) patients. Mitophagy is the programmed degradation of mitochondria, and is likely involved in drug resistance of cancer cells. Here, we identified hyperactivated mitophagy is essential for sorafenib resistance, and the mitophagy core regulator gene ATAD3A (ATPase family AAA domain containing 3A) was down regulated in hypoxia induced resistant HCC cells. Blocking mitophagy may restore… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Notwithstanding, unbalanced mitophagy may initiate and/or accelerate hepatocarcinogenesis to the extent that blocking mitophagy may restore Sorafenib sensitivity [174]. Huang et al showed that number of mitochondria in fission state was highly frequent in HCC tissues compared to adjacent non-tumors ones and these morphological alterations were accompanied by enhanced autophagic processes [133].…”
Section: Recovery Of Mitophagy In Hcc: Friend or Foe?mentioning
confidence: 99%
“…Notwithstanding, unbalanced mitophagy may initiate and/or accelerate hepatocarcinogenesis to the extent that blocking mitophagy may restore Sorafenib sensitivity [174]. Huang et al showed that number of mitochondria in fission state was highly frequent in HCC tissues compared to adjacent non-tumors ones and these morphological alterations were accompanied by enhanced autophagic processes [133].…”
Section: Recovery Of Mitophagy In Hcc: Friend or Foe?mentioning
confidence: 99%